More Frequent Vaginal Orgasm Is Associated with Experiencing Greater Excitement from Deep Vaginal Stimulation. (9th April 2013) - Brody, Stuart; Klapilova, Katerina; Krejčová, Lucie
Abstract Introduction Research indicated that: (i) vaginal orgasm (induced by penile–vaginal intercourse [PVI] without concurrent clitoral masturbation) consistency (vaginal orgasm consistency [VOC]; percentage of PVI occasions resulting in vaginal orgasm) is associated with mental attention to vaginal sensations during PVI, preference for a longer penis, and indices of psychological and physiological functioning, and (ii) clitoral, distal vaginal, and deep vaginal/cervical stimulation project via different peripheral nerves to different brain regions. Aims The aim of this study is to examine the association of VOC with: (i) sexual arousability perceived from deep vaginal stimulation (compared with middle and shallow vaginal stimulation and clitoral stimulation), and (ii) whether vaginal stimulation was present during the woman's first masturbation. Methods A sample of 75 Czech women (aged 18–36), provided details of recent VOC, site of genital stimulation during first masturbation, and their recent sexual arousability from the four genital sites. Main Outcome Measures The association of VOC with: (i) sexual arousability perceived from the four genital sites and (ii) involvement of vaginal stimulation in first‐ever masturbation. Results VOC was associated with greater sexual arousability from deep vaginal stimulation but not with sexual arousability from other genital sites. VOC was also associated with women's first masturbation incorporating (or being exclusively) vaginal stimulation. Conclusions The findings suggest (i) stimulating the vagina during early life masturbation might indicate individual readiness for developing greater vaginal responsiveness, leading to adult greater VOC, and (ii) current sensitivity of deep vaginal and cervical regions is associated with VOC, which might be due to some combination of different neurophysiological projections of the deep regions and their greater responsiveness to penile stimulation. Brody S, Klapilova K, and Krejčová L. More frequent vaginal orgasm is associated with experiencing greater excitement from deep vaginal stimulation. J Sex Med 2013;10:1730–1736.